The landscape of youth engagement in labor markets in Africa: Are youth driving structural transformation? - Abay, Kibrom A.; Wondale, Meseret; Korir, Josphat K.; Bachewe, Fantu Nisrane; Araya, Mesele; Breisinger, Clemens (International Food Policy Research Institute, 2025)
This paper assesses the landscape and evolution of youth engagement in labor markets in Africa, focusing on three important countries—Ethiopia, Kenya, and Nigeria—which together account for 40 percent of Africa’s youth population. We also examine whether Africa’s youth are driving structural transformation. To do so, we combine nationally representative data and surveys spanning more than two decades (from the 1990s to the 2020s). We situate the analysis within the region’s pressing youth unemployment challenge, where annual labor-force entrants surpass job creation. Our findings show that, despite substantial heterogeneities across countries, largely due to sectoral composition of economies, youth remain engaged in agriculture almost as much as adults. While labor continues to gradually shift out of agriculture, it has moved overwhelmingly into services rather than industry, reinforcing the unique pattern of structural transformation in Africa. More importantly, exit rates from agriculture are similar for youth and adults, except in Ethiopia, where youth are leaving agriculture at slightly higher rates than adults. In Ethiopia and Kenya, the entry rate into services is higher among young women, while entry into industry is higher among young men, suggesting distributional and equity implications of Africa’s ongoing structural transformation. These findings offer important insights and challenge simplistic views that youth are leaving agriculture in “droves” as well as the sometimes-embroidered perceptions of their role in that transformation. We discuss the implications of these findings for sustaining inclusive employment opportunities and argue that agriculture should remain central to job creation efforts in Africa.